1965
DOI: 10.1126/science.147.3662.1149
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Inhibition: Mechanism for the Production of Impaired Fat Absorption

Abstract: Treatment of rats with puromycin and acetoxycycloheximide results in a defect in intestinal lipid transport. Under these conditions rats given corn oil accumulate triglyceride within the intestinal cells and fail to develop the normal postprandial hyperlipemia. The observed interference in lipid transport appears to be a consequence of impaired chylomicron formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
2

Year Published

1966
1966
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(45 citation statements)
references
References 13 publications
4
38
1
2
Order By: Relevance
“…Since lipoproteins To document further the impaired transport of have been shown to be essential for the transport of tripalmitin after ACH treatment, we carried out long chain triglycerides from intestinal mucosa studies in which samples of portal and aortic blood (8,9), experiments were carried out with ACH were obtained 60 minutes after injection of tripalto determine the effect of impaired protein synthe-mitin into intestinal loops. The lipids were fracsis on the mucosal uptake and transfer of '4C-tionated by thin layer chromatography and samples labeled lipids from intestinal loops (Table VII).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lipoproteins To document further the impaired transport of have been shown to be essential for the transport of tripalmitin after ACH treatment, we carried out long chain triglycerides from intestinal mucosa studies in which samples of portal and aortic blood (8,9), experiments were carried out with ACH were obtained 60 minutes after injection of tripalto determine the effect of impaired protein synthe-mitin into intestinal loops. The lipids were fracsis on the mucosal uptake and transfer of '4C-tionated by thin layer chromatography and samples labeled lipids from intestinal loops (Table VII).…”
Section: Resultsmentioning
confidence: 99%
“…The proteins of the chylomicron are probably those synthesized within the intestinal mucosa (8). It has been demonstrated that after the administration of agents such as puromycin and ethionine, which inhibit protein and lipoprotein synthesis, the transport of long chain triglycerides is markedly impaired (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…the enterocytes involved were characterized by their low natural capacity to synthesize lipoproteins and to export them. It should also be mentioned that experimental inhibition of protein synthesis in mammals results m an enlargement of enterocytic chylomicrons (Glickman et al 1972) and to extensive development of l~p i d droplets (Sabesin & Isselbacher 1965, Friedman & Cardell 1972.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present work on sea bass Dicentrarchus labrax, a carnivorous fish with stomach, was to study in detail the deterioration of the proximal intestine, which is the site of lipid absorption, and to relate it as far as possible to disturbances in this phase of digestion. Many studies in mammals, particularly in humans, have shown links between histopathologies of the intestinal epithelium and natural or induced disturbances in fat digestion and absorption (Sabesin & Isselbacher 1965, Dobbins 1966, Shimoda et al 1968, Rubin 1971, Ament et al 1972, Friedman & Cardell 1977, Takahashi & Mizunuma 1984.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Isselbacher and Budz (1963), and Sabesin and Isselbacher (1965) tested the effect of known protein synthe sis inhibitors (puromycin, acetoxycycloheximide, and ethionine) on rats in vivo. Results were similar to those of the abetalipoproteinemia disorder in that there occurred an accumulation of triglycerides in intestinal cells, and a decrease in production of g-lipoprotein and in incorporation of C^^-leucine into protein.…”
Section: Intracellular Phasementioning
confidence: 99%